2022
DOI: 10.3389/fenvs.2022.841380
|View full text |Cite
|
Sign up to set email alerts
|

Does Firm Growth Impede or Expedite Insolvency Risk? A Mediated Moderation Model of Leverage Maturity and Potential Fixed Collaterals

Abstract: Business sustainability is compromised with an increase in insolvency risk. Firm growth is desirable, but it brings an associated bundle of high risks. We decomposed firm growth into internal and external growth and studied its impact on insolvency risk using a panel data set of 284 listed non-financial firms in Pakistan from 2013 to 2017. This study used the hierarchical multiple regression approach through panel corrected standard error (PCSE) and feasible generalized least squares estimators to test the pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 97 publications
(111 reference statements)
0
6
0
Order By: Relevance
“…After the world financial crisis in 2008, Chinese enterprises faced international and domestic pressure for their development, especially private enterprises with small scale and lower ability to resist risks, urgently need to increase foreign aid to fight risks jointly. The investigation found that the private enterprises acquired by state-owned capital face the direct risk of equity pledge and forced stock liquidation, and have deep hidden dangers such as insolvency and overdue bank loans [ 45 , 46 ]. After private enterprises join the state-owned platform, they can make use of the capital and technology advantages of state-owned enterprises and then take advantage of their management flexibility, which can not only relieve their debt pressure and solve the risk of equity pledge but also enable private enterprises to replenish capital, expand and reproduce, and continue to operate.…”
Section: Resultsmentioning
confidence: 99%
“…After the world financial crisis in 2008, Chinese enterprises faced international and domestic pressure for their development, especially private enterprises with small scale and lower ability to resist risks, urgently need to increase foreign aid to fight risks jointly. The investigation found that the private enterprises acquired by state-owned capital face the direct risk of equity pledge and forced stock liquidation, and have deep hidden dangers such as insolvency and overdue bank loans [ 45 , 46 ]. After private enterprises join the state-owned platform, they can make use of the capital and technology advantages of state-owned enterprises and then take advantage of their management flexibility, which can not only relieve their debt pressure and solve the risk of equity pledge but also enable private enterprises to replenish capital, expand and reproduce, and continue to operate.…”
Section: Resultsmentioning
confidence: 99%
“…Thirdly, PTR is the piecewise linear regression. In other words, the relationship between X and Y is divided by M. However, this model does not examine the function of M. Thus, in the subsequent research, I will follow the research of Hussain et al [53] and Xuezhou et al [54] to research the mediation of the sum of import and export and the unemployment rate (both are threshold variables of this study). Fourthly, many scholars, such as Zhang et al [55], have proved that green energy has a significant effect on economic development.…”
Section: Plos Onementioning
confidence: 99%
“…Third, government departments should strengthen capital market governance, improve the lending function of financial markets, and reduce the external financing costs of enterprises Wen et al, 2022), improve the functional attributes of financial markets and financial assets so that finance can return to the source of serving the real economy. Moreover, the government should eliminate the institutional credit financing discrimination brought by the form of ownership and strengthen the supervision over the allocation of financial assets by state-owned enterprises.…”
Section: Practical Implicationsmentioning
confidence: 99%